Mate extract as feed additive for improvement of beef quality. (September 2017) - de Zawadzki, Andressa; Arrivetti, Leandro O.R.; Vidal, Marília P.; Catai, Jonatan R.; Nassu, Renata T.; Tullio, Rymer R.; Berndt, Alexandre; Oliveira, Clayton R.; Ferreira, Antonio G.; Neves-Junior, Luiz F.; Colnago, Luiz A.; Skibsted, Leif H.; et al.
Abstract: Mate ( Ilex paraguariensis A.St.-Hil.) is generally recognized as safe (GRAS status) and has a high content of alkaloids, saponins, and phenolic acids. Addition of mate extract to broilers feed has been shown to increase the oxidative stability of chicken meat, however, its effect on beef quality from animals supplemented with mate extract has not been investigated so far. Addition of extract of mate to a standard maize/soy feed at a level of 0.5, 1.0 or 1.5% w /w to the diet of feedlot for cattle resulted in increased levels of inosine monophosphate, creatine and carnosine in the fresh meat. The content of total conjugated linoleic acid increased in the meat as mate extract concentration was increased in the feed. The tendency to radical formation in meat slurries as quantified by EPR spin-trapping decreased as increasing mate extract addition to feed, especially after storage of the meat, indicating higher oxidative stability. Mate supplementation in the diet did not affect animal performance and carcass characteristics, but meat from these animals was more tender and consequently more accepted by consumers. Mate extract is shown to be a promising additive to feedlot diets for cattle to improve the oxidative stability, nutritive value and sensory quality of beef. Graphical abstract: Highlights: Mate extract supplementation in animal feed affects metabolic pathways related to beef quality. Meat from cattle supplemented with mate extract shows increase oxidative stability. Beef from cattle supplemented with mate extract shows better sensory evaluation. Beef from cattle fed 1.5% mate extract shows better consumer acceptance.